2016
DOI: 10.1007/s00595-016-1369-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment technique of HyperEye medical system angiography for coronary artery bypass grafting

Abstract: Significant reductions in the ICG intensity rate and average acceleration value can occur in failed grafts. Therefore, quantifiable changes in ICG intensity may help detect minute changes in blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…We also reported that HEMS is not only used at the time of SLNB, but also in other surgery [28][29][30]. HEMS has been used for assessment of the bypass graft during cardiovascular surgery, blood supply evaluation of reconstructed organs, blood circulation confirmation for acute mesenteric ischemia, and identification of tumor location and anatomical variations in liver surgery [9,[28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…We also reported that HEMS is not only used at the time of SLNB, but also in other surgery [28][29][30]. HEMS has been used for assessment of the bypass graft during cardiovascular surgery, blood supply evaluation of reconstructed organs, blood circulation confirmation for acute mesenteric ischemia, and identification of tumor location and anatomical variations in liver surgery [9,[28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future studies should aim to establish more quantitative assessment methods such as measuring ICG intensity (8) or blood flow speed (9).…”
Section: Discussionmentioning
confidence: 99%
“…ICG opacification luminance intensity of the graft was quantitatively measured retrospectively 3 ) ( Fig. 3 ).…”
Section: Case Reportmentioning
confidence: 99%